Biocompatibility Study of a Commercial Printed Circuit Board for Biomedical Applications: Lab-on-PCB for Organotypic Retina Cultures - Jesús David Urbano-Gámez; Lourdes Valdés-Sánchez; Carmen Aracil; Berta de la Cerda; Francisco Perdigones; Álvaro Plaza Reyes; Francisco J. Díaz-Corrales; Isabel Relimpio López; José Manuel Quero (Micromachines, 2021)
Printed circuit board (PCB) technology is well known, reliable, and low-cost, and its application to biomedicine, which implies the integration of microfluidics and electronics, has led to Lab-on-PCB. However, the biocompatibility of the involved materials has to be examined if they are in contact with biological elements. In this paper, the solder mask (PSR-2000 CD02G/CA-25 CD01, Taiyo Ink (Suzhou) Co., Ltd., Suzhou, China) of a commercial PCB has been studied for retinal cultures. For this purpose, retinal explants have been cultured over this substrate, both on open and closed systems, with successful results. Cell viability data shows that the solder mask has no cytotoxic effect on the culture allowing the application of PCB as the substrate of customized microelectrode arrays (MEAs). Finally, a comparative study of the biocompatibility of the 3D printer Uniz zSG amber resin has also been carried out.